2019
DOI: 10.1507/endocrj.ej18-0252
|View full text |Cite
|
Sign up to set email alerts
|

Association of the muscle/fat mass ratio with insulin resistance in gestational diabetes mellitus

Abstract: This study assessed the association of muscle mass with insulin resistance, evaluated from the insulin sensitivity index (ISI), in Japanese patients with gestational diabetes mellitus (GDM). Consecutive patients with GDM (n = 96) admitted to St. Marianna University Hospital between October 2015 and March 2018 for initial education and glycemic control were enrolled in a prospective observational study. Insulin resistance was evaluated by measuring the ISI and body composition was assessed by bioelectrical impe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…[26][27][28] However, previous studies have shown that the Chinese population, like other Asian populations, has a lower BMI but a higher percentage of body fat than Caucasians of similar age and gender. 29 BMI does not differentiate between bone, muscle, and fat mass, so a simple and inexpensive method of assessing fat mass may be better for predicting the development of GDM. Methods such as bioelectrical impedance analysis for the assessment of fat mass and fat-free mass in pregnant women in the body composition studies have been described.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] However, previous studies have shown that the Chinese population, like other Asian populations, has a lower BMI but a higher percentage of body fat than Caucasians of similar age and gender. 29 BMI does not differentiate between bone, muscle, and fat mass, so a simple and inexpensive method of assessing fat mass may be better for predicting the development of GDM. Methods such as bioelectrical impedance analysis for the assessment of fat mass and fat-free mass in pregnant women in the body composition studies have been described.…”
Section: Dovepressmentioning
confidence: 99%
“…According to a study conducted by Kawanabe et al, inadequate appendicular skeletal muscle mass/fat mass ratio is a risk for the development of insulin resistance in Japanese patients with GDM. 29 Unfortunately, we did not evaluate the relationship between SMMP and insulin resistance since insulin test is not included in the routine Figure 2 Correlation between pre-BMI and FMI and receiver-operating characteristic (ROC) curve to predict GDM. (A) Correlation between Pre-BMI and FMI.…”
Section: Dovepressmentioning
confidence: 99%
“…Several studies have demonstrated that high muscle mass, high muscle/fat mass ratio and high muscle strength are associated with lower insulin resistance in a variety of populations (36)(37)(38)(39). On top of this, it has been demonstrated in several studies that low muscle strength is associated with a higher prevalence and severity of type 2 diabetes in a broad range of ethnicities (40-45).…”
Section: Muscle Mass/function and Risk Of Type 2 Diabetesmentioning
confidence: 99%
“…Diabetes is characterized by multiple mutagenic events that affect the secretion and sensitivity of insulin. Moreover, diabetes is known to be associated with various diseases in different tissues and organs, including kidney, skeleton muscle, eyes, lung, heart, liver, and even brain [142,143,144,145,146,147,148]. The protein Cdc42 is a member of the Rho family of small GTPases.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%